Expression of genes involved in immune regulation in chronic myeloid leukemia - Giang, Nguyen Hoang; Thanh Huyen, Nguyen; Xuan, Nguyen Thi (Vietnam Journal of Biotechnology, 2021)
Chronic myeloid leukemia (CML) is a blood cancer involved in abnormal proliferation of myeloid cells at all stages of differentiation. Translocation of regions of the BCR and ABL genes, leading to the fusion gene BCR-ABL, which forms the Philadelphia (Ph) chromosome, is the cause of more than 90% of CML. The BCR-ABL protein shows abnormal tyrosine kinase activity, leading to changes in proliferation signals including signal transducer and activator of transcriptions (STATs) and nuclear factor kappa-light-chain-enhancer of activated B (NF-κB) and resulting in uncontrolled proliferation of myeloid cells. CTLA-4, PD-1 and LAG3 genes are known as immunosuppressive receptors playing important roles in controlling immune response by inhibiting activity of T helper cells. Klotho gene has anti-aging, anti-inflammatory and anti-cancer functions. STAT signaling pathway genes regulate cancer cell functions by their phosphorylation and IκB-α gene by degradation of its expression. In this study, we conducted experiments to determine mRNA expression of these genes on immune cells in CML patients by using realtime-PCR. Results showed a marked increase in the expression of STAT-1 and STAT-6 signaling genes and a decreased LAG3 expression in CML patients as compared with healthy controls. In addition, other gene expressions such as CTLA4, PD1, klotho, IκB-α, STAT3 and STAT5 were unaltered in CML cells. The abnormal increased expression of STAT1 and STAT6 genes indicated an important role of these signaling genes in regulating activity of immune cells, leading to pathogenesis and development of CML disease. The evidence suggested that STAT-1 and STAT-6 genes could be important and potential markers in early prognosis of CML.